Equity Crowdfunding as an Alternative Source of Financing Entrepreneurship in the Greater Accra Region of Ghana - Joseph Yensu; Kyei Baffour Asare; Daniel Abayaakadina Atuilik; George Asumadu (European Scientific Journal, ESJ, 2023)
Entrepreneurship is globally seen as a tool for job creation and contributing to the stability of the economies of nations. This is why the governments of many nations including Ghana put up initiatives to promote entrepreneurial activities. This work sought to assess equity crowdfunding as an alternative source of generating fund for entrepreneurial projects in Ghana. A combination of qualitative and quantitative approaches were used in conducting this study in the Tema Municipality of the Greater Accra Region due to the intense commercial activity in that area. Out of a population of 10,000  entrepreneurs and investors, a sample size of 149 entrepreneurs in various industries and 118 investors as well as 90 respondents acting as both entrepreneurs and investors were chosen through purposive sampling method. Data was collected through the use of questionnaires and was analysed by way of descriptive stattistics using tables and graphs. The results of the study showed that most entrepreneurs and investors had heard of equity crowdfunding but very few understood the operations of this type of funding. Also, most respondents saw one of the challenges in the adoption of crowdfunding in Ghana to be inadequateunderstanding of it among entrepreneurs and investors.  It is evident from the study that the level of awareness of equity crowdfunding in the entrepreneurship community in Ghana is low. The study showed that equity crowdfunding is capable of bridging the funding gap and therefore a suitable alternative in generating funds for entrepreneurship in Ghana. It is recommended that equity crowdfunding be included as a source of funding in entrepreneurship curriculum. Also, policies should be made by government to establish regulations that will protect all the parties involved in equity crowdfunding.